Augmented Cardiac Mitochondrial Capacity in High Capacity Aerobic Running “Disease-Resistant” Phenotype at Rest Is Lost Following Ischemia Reperfusion - Alsahly, Musaad B.; Zakari, Madaniah O.; Koch, Lauren G.; Britton, Steven; Katwa, Laxmansa C.; Fisher-Wellman, Kelsey; Lust, Robert M. (Frontiers in Cardiovascular Medicine, 2021)
Animal models demonstrating either high (HCR) and low (LCR) aerobic running capacity phenotypes have been developed to study the intrinsic contribution, with HCR rats subsequently characterized as “disease resistant”, and the LCRs as “disease prone”. Enhanced cardioprotection in HCRs has been variable and mutifactoral, but likely includes a metabolic component. These studies were conducted to determine the influence of intrinsic aerobic phenotype on cardiac mitochondrial function before and after ischemia and reperfusion. 34 HCR and LCR rats were randomly assigned to either control or ischemia/reperfusion (IR). On each study day, one HCR/LCR pair was anesthetized, and hearts were rapidly excised. In IR animals, hearts were immediately flushed with iced hyperkalemic, hyperosmotic, cardioplegia solution, and subjected to global hypothermic ischemic arrest (80 min). Following arrest, the hearts underwent warm reperfusion (120 min) using a Langendorff perfusion system. Following reperfusion, the heart was weighed, the LV was isolated, infarct size was determined (TTC) and mitochodria were isolated. for respiratory studies (Oroboros). In control animals, MITO were obtained and prepared in similar fashion but without IR. In control rats, both resting and maximally stimulated MITO respiratory rates were higher (32% and 40%, respectively; p <0.05) in HCR compared to LCR. After IR, MITO respiratory rates were decreased to about 10% of control in both strains, and the augmented capacity in HCRs was absent. Maximally stimulated rates also were decreased more than 50% from control and were no longer different between phenotypes. Ca++ retention capacity and infarct size were not significantly different between HCR and LCR (49.2% ± 5.6 vs. 53.7% ± 4.9). Conclusion: Cardiac mitochondria from HCR were significantly higher in control conditions with each substrate tested. After IR insult, the cardiac mitochondrial respiratory rates were similar between phenotypes, as was Ca++ retention capacity and infract size. Relatively, the loss of respiratory capacity was actually greater in HCR than LCR. Together, these data could suggest limits in the extent to which the HCR phenotype might be “protective” against acute tissue stressors. The extent to which any of these deficits could be “rescued” by an active exercise component is unknown.